Understanding mobile phone case evaluative criteria of US Millennials. Issue 1 (2nd January 2016) - Hahn, Kim; Kim, Jihyun
ABSTRACT: Millennials are the crucial market segment in mobile marketing and retail industry due to their heavy usage and higher dependency on mobile devices. The purpose of this study was to investigate the influence of personal traits of college students with different majors on mobile phone case evaluative criteria. Five hundred-and-nine college students were recruited as participants in various disciplines/majors using a non-representative, convenience sampling technique. Findings showed that fashion majors exhibited higher levels of personal traits variables that were themed around fashion, such as self-monitoring tendency, fashion involvement, and proclivity to experiment with appearance, compared to non-fashion majors. Fashion majors were found to be significantly more dependent on their mobile devices, compared to non-fashion students. These findings provide valuable information to help the mobile phone industry understand young consumers' evaluation criteria and develop their product and marketing strategy accordingly.